The Description of Larva Free Index as COMBI (Communication for Behavioral Impact) Dengue Hemorrhagic Fever Prevention Indicator - Suryanegara, Fithria Dyah Ayu; Suparmi, Suparmi; Setyaningrum, Ndaru (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Dengue hemorrhagic fever (DHF) has a high incidence rate, especially in the tropical and subtropical area. Various efforts have been made as an attempt to empower the community in PSN-dengue program, but has not yet reached the optimal result. COMBI (Communication for Behavioral Impact) is a dynamic team working to formulate and deliver the message, materials, and appropriate communication media for community problems found by way of a mutually agreed settlement of the problem.Quantitative research was done by cross sectional method to check the water storage containers inside the houses of the respondents. The number of the respondents were 990 male (38.1%), 1612 female (61.9%). Three (0.1%) respondents were aged <17 years, 249 (9.6%) were 17-25 years old, 526 (20.2%) were 26-35 years old, 706 (27.1%) were 36-45 years old, 602 (23.1%) were 46-55 years old, 348 (13.4%) were 56-65 years old, 173 (6.7%) were >65 years old. Most dominant level of education and employment statuses were 1107 (42.5%) high school and 858 (32.9%) were housewives. The average numbers of Larva Free Index in Sleman Regency, Bantul Regency and Yogyakarta municipality were - 75.8%; 70.9%; and 77.3% respectively. The average CI in Yogyakarta municipality was 7.05%, Sleman Regency was 9.68%, and Bantul Regency was 20.86%. The average HI in Yogyakarta municipality was 22.7%, Sleman Regency was 24.13%, and Bantul Regency was 29.02%. This study suggested that the LFI, CI and HI were not in accordance with the target of the Ministry of Health.